"UNLOCKING THE POWER OF NEUROBIOLOGY: ENHANCING RELATIONAL DYNAMICS AND CONFLICT RESOLUTION THROUGH HORMONAL INSIGHTS, GENETIC FACTORS, AND STRESS MANAGEMENT STRATEGIES IN PRENUPTIAL AGREEMENTS" (CAHIERS MAGELLANES-NS, 2024)
The application of neurobiological research to relational dynamics offers a new and transformative view of prenuptial agreements. Prenuptial agreements are normally seen as precautions in legal forms meant to save individuals’ assets as well indicating financial obligations in cases of divorce. Although these agreements continually stress for economic security and fairness, they frequently disregard the underlying psychological and emotional aspects that significantly affect the stability of marriage. Recent progress made in neurobiology can help improve the effectiveness of pre-nuptials by incorporating markers of conflict from within biology. This paper examines potentially leveraging biological insights garnered from neurobiology towards creation and enforcement of pre-nuptials with the aim to foster healthier and more resilient marital relationships. The research looks at key biological markers such as hormonal levels, genetic factors, and neurobiological indicators to appreciate their effects on relationship dynamics including testosterone (T), oxytocin (OT) and cortisol (C). For example, cortisol regulates stress response while oxytocin influences bonding, which may affect conflict proneness or emotional connection between partners.